The Effect of Cone Drill Training on Agility Futsal Players University of Lambung Mangkurat - Ramadhan Arifin; Hasyim Hasyim; Nurdiansyah Nurdiansyah (UNIB Press, 2022)
This study aims to determine whether there is an effect of Cone Drill exercise on the agility of Futsal Players at Lambung Managkurat University. The method used in this study is a pre-experimental design method with the Zig-zag Run Test instrument. The research design used pretest and posttest in one group. The population in this study were all futsal players who took part in the training, totaling 12 people and the sample being 12 people. Sampling was done by total sampling technique. The results of the initial test data conducted by futsal players at Lambung Mangkurat university with the fastest time of 9.10 seconds, the longest time of 10.36 seconds and the average initial test time of 9.66 seconds. Whereas in the final test of agility abilities carried out by futsal players, the fastest time is 8.12 seconds, the longest time is 9.45 seconds with an average final test time of 8.52 seconds. The results of data analysis show that there is an effect of Cone Drill training on the agility of futsal players at Lambung Mangkurat University.